Food, gastronomy, sustainability, and social and cultural development cross-disciplinary perspectives (London, United Kingdom Academic Press, an imprint of Elsevier, 2023)
"Food, Gastronomy, Sustainability, and Social and Cultural Development analyzes the relationship between gastronomy and sustainability from a sociocultural perspective. It uses practical case studies to reveal the connection between food, society, culture, and the impact they have with each other. Beginning with the introduction of the relationship among gastronomy, sustainability, culture, and contemporary controversies, this book expands topics from binomial gastronomy at local level, impact of sustainability on gastronomic experiences, an evaluation of production systems to the role of gastronomy, and sustainability in tourism. The role of technology in food and sustainability, health, ideologies, and social movements surrounding gastronomy are also widely discussed. This book is a valuable reference for food scientists, undergraduate and graduate students, and industrial professionals working in the food processing field." --
1. Gastronomy, sustainability, culture. An introduction to contemporary debates
2. Gastronomy, seasonality, localism, and sustainability: lessons from a long memory, a pandemic, and a current war
3. Why is environmental sustainability not possible without social sustainability? Food, sustainable diets, and sociocultural perspectives in the Mediterranean area
4. Sustainability at the menu of Malaysian, Indonesian, and Singaporean top chefs
5. Sustainable diets: intergenerational challenges from the Global South
6. Exploring tourists and local consumers¿ attitudes on service automation in restaurant industry: the Spanish fast-food experience
7. Sustainable restaurants in Barcelona (Spain): identity and sustainability in local cuisine
8. The cuisine of the new spirit of capitalism: Noma considerations regarding the value of the authentic and other orders of worth
9. Food on wheels: culinary paths toward sustainable lives for migrants in Germany
10. Agrifood routes as tools for sustainable rural development: the case of chili route in Yahualica Denomination of Origin
11. Gastronomic tourism and alternative food networks: a contribution to the Agenda 2030
12. Gastronomic tradition, sustainability, and development: an ethnographic perspective of gastronomy in Las Hurdes (Extremadura, Spain)
13. Eating and thinking at the same time: food consumption and sustainability in Lugo (Galicia, Spain)
14. The Organic Market of Mazatlan (Sinaloa, Mexico). Paradoxes of food supply, tourism, and migration
Includes bibliographical references and index
Keywords: Medina, F. Xavier; Conde-Caballero, David; Mariano-Juarez, Lorenzo; Sustainable food systems; Gastronomy -- Social aspects; Food consumptions -- Environmental aspects